Impatiens rubricaulis (Balsaminaceae), a new species of Impatiens from West Sumatra - Nanda Utami (BRIN Publishing (Penerbit BRIN), 2009)
Impatiens rubricaulis Utami (Balsaminaceae) is described as a new species.